2023
DOI: 10.1590/1678-7757-2022-0323
|View full text |Cite
|
Sign up to set email alerts
|

Can composite packaging and selective enamel etching affect the clinical behavior of bulk-fill composite resin in posterior restorations? 24-month results of a randomized clinical trial

Abstract: Objectives This is a double-blind, split-mouth, randomized clinical study that aims to evaluate the influence of bulk-fill composite packaging presented in syringes (BSy) and capsules (BCa), and the effect of selective enamel etching (SEE) on the clinical performance of class I and II bulk-fill resin composite restorations after 24 months. Methodology A total of 295 class I or class II restorations were performed on 70 patients. One universal adhesive was applied in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…In relation to the color match, intergroup comparisons of both materials have revealed statistically significant variations over three monitoring time frames: the starting point, six, and twelve months Which was in match with the examination managed by Balkaya et al, that reported that the color and translucency qualities of HVGIC restorations were still insufficient, and their color match was not exactly the same as composite resin restorations [8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 54%
“…In relation to the color match, intergroup comparisons of both materials have revealed statistically significant variations over three monitoring time frames: the starting point, six, and twelve months Which was in match with the examination managed by Balkaya et al, that reported that the color and translucency qualities of HVGIC restorations were still insufficient, and their color match was not exactly the same as composite resin restorations [8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 54%
“…5 Perceptibility/acceptability thresholds were considered for ΔE ab and ΔE 00 (1.2/2.7 and 0.8/1.8, respectively), in order to evaluate overall color change. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The ΔE ab and ΔE 00 values after brushing were significantly higher for the RT than the HP group.…”
Section: Discussionmentioning
confidence: 99%
“… 5 The use of bulk-fill composites in clinical practice is an attractive proposition since single increments of 4–5 mm thickness can be cured by light, resulting in a consequential reduction in clinical time. 6 - 7 The basic aesthetic and surface characteristics of these composites, mostly color alteration, gloss, and roughness, are important factors that can affect the longevity and replacement of the restorations. 8 The decrease in composite properties may be associated with adverse conditions existing in the oral cavity, such as attritional wear promoted by masticatory forces, toothbrushing, and changes in temperature and pH of the oral environment.…”
Section: Introductionmentioning
confidence: 99%